Scale-up of milling in a 100 L device for processing of TiFeMn alloy for hydrogen storage applications: Procedure and characterization. (8th November 2019) - Bellosta von Colbe, José M.; Puszkiel, Julián; Capurso, Giovanni; Franz, Andreas; Benz, Hans Ulrich; Zoz, Henning; Klassen, Thomas; Dornheim, Martin
Abstract: In this work, the mechanical milling of a FeTiMn alloy for hydrogen storage purposes was performed in an industrial milling device. The TiFe hydride is interesting from the technological standpoint because of the abundance and the low cost of its constituent elements Ti and Fe, as well as its high volumetric hydrogen capacity. However, TiFe is difficult to activate, usually requiring a thermal treatment above 400 °C. A TiFeMn alloy milled for just 10 min in a 100 L industrial milling device showed excellent hydrogen storage properties without any thermal treatment. The as-milled TiFeMn alloy did not need any activation procedure and showed fast kinetic behavior and good cycling stability. Microstructural and morphological characterization of the as-received and as-milled TiFeMn alloys revealed that the material presents reduced particle and crystallite sizes, even after such short time of milling. The refined microstructure of the as-milled TiFeMn is deemed to account for the improved hydrogen absorption-desorption properties. Highlights: First industrial-sized milling treatment procedure for TiFe alloys reported. Milled alloy does not need thermal activation. Milled alloy shows superior H2 sorption behavior vs. thermally treated alloy. Procedure is easily scalable to larger mills.